Treatment for Trigeminal Neuralgia Revisited for Longer Remission: A Series of 56 Cases - Gursimrat K. Brar; S. P. S. Sodhi (Wolters Kluwer Medknow Publications, 2024)
The primary challenge associated with peripheral neurectomy is the occurrence of spontaneous nerve regeneration. This study focused on addressing this issue by employing a novel approach involving the use of sticky (steaky) bone to obliterate the foramina post-peripheral neurectomy. The study involved 56 patients diagnosed with trigeminal neuralgia, divided into two groups. In group I, the proximal nerve stump in the foramina was chemically cauterized after peripheral neurectomy, while in group II, sticky bone was used to obliterate the foramina. After a 2-year follow-up period, group II exhibited a significant improvement in the mean Visual Analogue Scale scores. Additionally, cone-beam computed tomography analysis revealed a noteworthy reduction in the size of the foramina in group II at 2 years post-operatively.